An - David R. Anderson (Thomson, 2007)
A Quantitative Approach to Decision Making provides thorough, application-oriented coverage in a very readable writing style. This is the leading text on the market. Simply put, it's a classic! The problem-scenario approach introduces quantitative procedures through situations that include both problem formulation and technique application